ANALYSIS SUFFIXES ON REPORT TEXT “WASHINGTON D.C” - Rajagukguk, Fretty Riana; Purba, Irene Stefani Mutiara; Sitepu, Rachel Yolanda; Sitanggang, Anita (Transpublika Publisher, 2022)
Suffix is one component that can be used to form new words in English. The suffix used in this case is a beginning suffix. The purpose of this study to finding the form, function and meaning of the beginning suffix found in